Al-WalÄ` in Islamic Inheritance Law: Looking for Its Legal Effects - Muhammad Habibi Miftakhul Marwa (Jurnal Hukum Novelty, 2020)
Introduction to The Problem: Slaves and slavery had existed since before Islam preached by Muhammad (PBUH). Islam provides gradual problem-solving methods regarding slavery; one of them is through inheritance. In Islamic Law terms, it called al-walÄâ€™ or liberated slaves. The slave that freed by the master will gain the estate from him. However, slavery is now viewed as merely an academic discourse since it is considered no longer exist.Purpose/Objective Study: The purpose of this research is to find out the legal standing and legal effect of al- walÄâ€™ in the Islamic Inheritance Law.Design/Methodology/Approach: This study is classified as a normative study. The study employed secondary data obtained from the literature review on al- walÄ,â€™ and it analyzed descriptively using the conceptual approach.Findings: The study found that the substance for al- walÄâ€™ in the Islamic Inheritance Law of inheritance is to liberate slavery through legal descent-based kinship (nasab á¸¥ukmÄ«). A person who frees the slaves holds al- walÄâ€™ right. Accordingly, he has the right to inherit the slaveâ€™s wealth when the slave dies and does not have any inheritors. Second, al- walÄâ€™ brings a legal effect on the freed slaves, namely, the person who releases the slave, the slaveâ€™s left wealth, guardianship, legal competence, and the inheritance itself.